Experimental and numerical study of basalt fiber reinforced polymer strip strengthened autoclaved aerated concrete masonry walls under vented gas explosions. (1st December 2017) - Li, Zhan; Chen, Li; Fang, Qin; Chen, Wensu; Hao, Hong; Zhang, Yadong
Highlights: Field tests of BFRP strengthened AAC masonry walls under gas explosions were conducted. The performances of wall specimens were investigated to evaluate BFRP strengthening. Numerical model of strengthened masonry walls under gas explosion was calibrated. Parametric studies of strengthened masonry walls were carried out with the calibrated model. Abstract: Ten full-scale field tests were conducted to study the performance of basalt fiber reinforced polymer (BFRP) strip strengthened autoclaved aerated concrete (AAC) masonry walls subjected to vented gas explosions. Three walls i.e. unstrengthened, rear-face strengthened and front-face strengthened wall specimens were prepared for blast tests. The testing data including overpressure time histories of vented gas explosions, displacement time histories, damage characteristics and fragment distribution of each wall specimen were recorded and analyzed. It was found that the rear-face strengthened wall specimen showed the best blast-resistant performances. Three wall specimens under vented gas explosions experienced damage modes of typical two-way flexural deformation along with shattering of AAC blocks at the latter stage of gas explosions. A detailed micro model for masonry walls was developed in LS-DYNA, incorporating material parameters obtained from material tests. The accuracy of numerical model in predicting the responses of masonry walls was validated with the testing data. Parametric studies were also conducted to explore the influences of BFRP strip layouts, strip thickness and fiber types on the performances of masonry walls. It is found that the BFRP strip layout, strip thickness and fiber types affect the resistance capacity of masonry walls significantly.